Improvements in health-related quality of life following a group intervention for coping with AIDS-bereavement among HIV-infected men and women. - Sikkema, Kathleen J; Hansen, Nathan B; Meade, Christina S; Kochman, Arlene; Lee, Rachel S (Quality of life research : an international journal of quality of life aspects of treatment, care and rehabilitation, 2005)
AIDS-related bereavement is a severe life stressor that may be particularly distressing to persons themselves infected with HIV. Increasing evidence suggests that psychological health is associated with disease progression, HIV-related symptoms, and mortality.
Keywords: Adaptation, Psychological; Adult; Bereavement; Disease Progression; Female; HIV Seropositivity; Humans; Male; Middle Aged; Psychotherapy; Quality of Life; Self-Help Groups; Sickness Impact Profile; Treatment Outcome; United States